2015
DOI: 10.1039/c4mt00326h
|View full text |Cite
|
Sign up to set email alerts
|

Protection from neurodegeneration in the 6-hydroxydopamine (6-OHDA) model of Parkinson's with novel 1-hydroxypyridin-2-one metal chelators

Abstract: Brain iron accumulation has been associated with inciting the generation of oxidative stress in a host of chronic neurological diseases, including Parkinson's disease. Using the catecholaminergic neurotoxin 6-hydroxydopamine to lesion cellular dopaminergic pathways as a model of Parkinson's disease in culture, a selection of 1-hydroxypyridin-2-one (1,2-HOPO) metal chelators were synthesized and their neuroprotective properties were compared to the 3-hydroxypyridin-4-one; deferiprone (3,4-HOPO; DFP). Protection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 55 publications
(79 reference statements)
1
34
0
Order By: Relevance
“…To try and establish spectroscopic features that would allow us to distinguish an N 3 O 3 from an O 6 coordination mode, we were forced to first investigate by MS and NMR the complexation of Ga(III) on a model system. Compound 22 that we described for another type of application has been selected as such a model of ligand 19 [63].…”
Section: Organic Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…To try and establish spectroscopic features that would allow us to distinguish an N 3 O 3 from an O 6 coordination mode, we were forced to first investigate by MS and NMR the complexation of Ga(III) on a model system. Compound 22 that we described for another type of application has been selected as such a model of ligand 19 [63].…”
Section: Organic Synthesismentioning
confidence: 99%
“…It was considered that deprotection can be afforded under a range of relatively mild conditions by double bond isomerisation and subsequent hydrolysis without compromising other bonds in the chelator [62]. The key allyl protected 6-hydroxymethyl intermediate 17 was synthesised in five steps from commercially available 12 (Scheme 2) [63]. This hydroxymethyl derivative could then be converted to the novel chloromethyl derivative 17 by thionyl chloride for incorporation onto ligand cores.…”
Section: Organic Synthesismentioning
confidence: 99%
“…Deferiprone is an orally available iron chelator that is currently in clinical use and has been shown to cross the BBB. In animal models of Parkinson's disease, it has been shown to improve motor performance (Aguirre et al, 2015;Ayton, Lei, Duce, et al, 2013;Ayton, Lei, et al, 2015;Devos et al, 2014;Dexter et al, 2011;Workman et al, 2015). Deferiprone is neuroprotective in neuronal culture models of Aβ toxicity (Molina-Holgado, Gaeta, Francis, Williams, & Hider, 2008;Part et al, 2015), and it has been shown to reduce Aβ burden and tau phosphorylation in a rabbit model of AD (Prasanthi et al, 2012).…”
Section: Ironmentioning
confidence: 99%
“…Also, Nrf2 inactivation connected with aging that was the main risk factor for PD . In detail, Nrf2 was located in the cytosol of substantia nigra dopaminergic neurons, whereas in age‐matched neurodegenerative diseases patients . Furtherly, it was found in the nucleus of the Nrf2 signaling, represented by NQO1 and HO‐1 expressions, was upregulated, implying an attempt to enhance brain protection via this pathway .…”
Section: Discussionmentioning
confidence: 99%